Microbiome: Finding common connections: Ecological associations among gut bacteria are largely consistent across hosts in a population of wild baboons - Santiago MA Francesca M; Raulo Aura (eLIFE SCIENCES PUBL LTD, 2025)
Ecological associations among gut bacteria are largely consistent across hosts in a population of wild baboons.